Assessing Monetary Policy Effects on the Financial System Stability of Armenia - Avetisyan, Marine («Տնտեսագետ» հրատ․)
This paper focuses on the impact of the monetary policy of the Central Bank of the Republic of Armenia on the stability of the Armenian financial system. This study aims to investigate and assess the relationship between monetary policy and the financial stability index, which we have constructed. The Principal Components Analysis (PCA) method was used to obtain the financial stability index. We used the Vector Autoregressive (VAR) modeling methodology based on annual data for the assessments. An impulse response function was constructed to evaluate how inflation shocks affect the financial stability index over time. By assessing the response of the financial stability index, we modeled the inflation shock, considered an intermediate tool of monetary policy, for the years 2013-2023; we noted that price stability policy has an impact on financial stability policy in Armenia. Specifically, with VAR modeling, the financial stability index responds positively to a one-time inflation shock, with the effects felt for about four years. However, the financial stability index deteriorates after that, assuming negative values. The results indicate that in an inflationary environment, when the economy is in an upward phase, financial stability will be at a high level for several years, but this will be followed by a phase of decline and instability, which many countries worldwide have faced.
Keywords: Finance